Vulvar squamous cell carcinoma: The role of p53 and p16 immunohistochemistry - Helena M Obermair; James Elhindi; Alison Brand; Unine Herbst (Elsevier, 2024)
Vulvar squamous cell carcinomas (SCC) represent a heterogeneous group of patients with implications for prognosis and response to treatment. Human papillomavirus (HPV)-associated SCC is characterised by p16 positivity, whereas non-HPV SCC often shows aberrant p53 expression. We conducted a retrospective analysis involving 148 patients with vulvar SCC from two Gynecologic Oncology units from Sydney, Australia. Patients' demographics, tumor characteristics, types of treatment and survival were analyzed and compared to p16 and p53 immunohistochemistry status. The p16-positive group was younger and included a higher prevalence of smokers, while the p53-positive group demonstrated greater comorbidity indices and was associated with tumor features that are independently related to poor prognosis. Compared to p16-positive patients our study has shown significantly higher recurrence rates and lower overall survival in the p53-positive group. Our findings support existing literature, emphasizing the prognostic significance of p16 and p53 in vulvar SCC. Despite the retrospective nature and variations in immunohistochemistry reporting, our study provides valuable insights into patient outcomes, particularly in a demographically diverse population. Future research, like the STRIVE trial, may determine if implementation of p16 and p53 stratified management algorithm will improve outcomes for women with vulvar SCC (McAlpine, 2024).